A new montane species of Cercosaura (Squamata: Gymnophthalmidae) from Colombia, with notes on the distribution of the genus - Doan, Tiffany M.; Lamar, William W. (Zootaxa, 2012)
The gymnophthalmid genus Cercosaura is distributed throughout South America and southern Panama. Cercosaurahypnoides sp. nov. was discovered from Meta, Colombia and differs from all other species by possessing threesupraoculars, a single palpebral scale, five supralabials and infralabials, hexagonal, keeled dorsal scales arranged intransverse and oblique rows, small lateral scales, six longitudinal rows of ventrals, 8–12 femoral pores per hindlimb,18–22 subdigital lamellae on the fourth toe, overlapping limbs when adpressed against the body, and the pattern of twodorsolateral and two lateral stripes throughout the head, body, and tail. The description of the new species increases the known number of Cercosaura species to 13, with five species occurring in Colombia.